Legal Characters of Partnership Agreement 212 Mart - Mulhadi Mulhadi; Zulkifli Sembiring (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2019)
AbstractBased on partnership principles, partnership agreements can take place when one or more people have the same interests and awareness to work together to achieve common interests. Although the national economic conditions are currently experiencing a significant decline with low public purchasing power, which is marked by the many closures of retail businesses, but the desire to build a business in the form of partnership in this sector in certain groups of people is still showing encouraging development. One of them is the spirit of partnership in the establishment of 212 Mart Supermarkets in Indonesia, especially Medan City. This study uses a normative juridical approach, which is nature descriptive because it seeks to explain clearly the pattern of the agreement of establishing 212 Mart supermarkets, where the population is 218 agreement documents. The sample selection was determined purposively because of the form and content of the same agreement from each investor from several 212 Mart Supermarkets that had been established in Medan City. Based on research shown that partnership agreement 212 Mart has several legal characters namely that partnership agreement 212 mart was identified as an unnamed (anonymous) agreement, reciprocal agreement, as an agreement which gave birth to new partnerships, and jamaat-based agreements.Keywords: legal characters, partnership, agreement, 212 Mart Abstrak:Berdasarkan prinsip-prinsip kemitraan, perjanjian kemitraan dapat terjadi ketika satu atau lebih orang memiliki minat dan kesadaran yang sama untuk bekerjasama untuk mencapai kepentingan bersama. Meskipun kondisi ekonomi nasional saat ini mengalami penurunan yang signifikan dengan daya beli masyarakat yang rendah, yang ditandai dengan banyaknya penutupan bisnis ritel, tetapi keinginan untuk membangun bisnis dalam bentuk kemitraan di sektor ini dalam kelompok orang tertentu masih menunjukkan perkembangan yang menggembirakan. Salah satunya adalah semangat kemitraan dalam pendirian Swalayan 212 Mart di Indonesia, khususnya Kota Medan. Penelitian ini menggunakan pendekatan yuridis normatif, yang sifatnya deskriptif karena berupaya menggambarkan secara jelas pola perjanjian pendirian Swalayan 212 Mart, di mana populasinya merujuk pada 218 dokumen perjanjian. Pemilihan sampel ditentukan secara purposif karena bentuk dan isi perjanjiannya serupa dari masing-masing investor dari beberapa Swalayan 212 Mart yang telah didirikan di Kota Medan. Berdasarkan penelitian menunjukkan bahwa perjanjian kemitraan 212 Mart memiliki beberapa karakter hukum yaitu bahwa perjanjian kemitraan 212 mart diidentifikasi sebagai perjanjian tanpa nama, perjanjian timbal balik, sebagai perjanjian yang melahirkan kemitraan baru, dan perjanjian berbasis jamaah.Kata kunci : Karakter Hukum, Perjanjian, Kemitraan, 212 Mart Аннотация:Основанный на принципах партнёрства, договор о партнёрстве может заключаться, когда один или несколько человек имеют одинаковые интересы и осведомленность о совместной работе с целью достижения общих интересов. Хотя текущее состояние экономики страны значительно ухудшилось из-за низкой покупательской способности, которая отмечена высоким количеством провала розничных предприятий, однако стремление построить бизнес в форме партнёрских отношений в этом секторе для нескольких определенных групп людей всё ещё проявляет обнадеживающее развитие. Одним из них является партнёрство в строительстве супермаркетов 212 в Индонезии, особенно в городе Медан. В этом исследовании используется нормативно-юридический подход посредством описательного характера, поскольку оно стремится чётко описать схему договора о строительстве супермаркетов 212, где их совокупность ссылается на 218 документов соглашения. Выбор образца был определён целенаправленно, потому что формa и содержаниe договора от каждого инвестора из нескольких супермаркетов 212, которые были построены в городе Медан, являются одинаковыми. На основании исследования показывается, что договор о партнёрстве супермаркетов 212 имеет несколько юридических характеров, а именно то, что договор о партнёрстве супермаркетов 212 идентифицируется как договор без указания имени, договор на основе взаимности, договор, который породил новое партнёрство, и коллективный договор.Ключевые Слова: юридический характер, договор, партнёрство, супермаркет 212